PENGARUH KUALITAS PRODUK DAN DESAIN PRODUK TERHADAP LOYALITAS KONSUMEN - Dini Anggraini (Universitas Riau Kepulauan, 2018)
This study was conducted to determine the condition of the telecommunications industry in the field of business competition intensifies over time, which makes telecommunications companies vying to create marketing strategies that aim to sustain new and achieve a better market share again. As for the problem of this research is